From Aluffi, Algebra: Chapter $0$

If $s$ is any element of a ring $S$, then there is a unique ring homomorphism $\mathbb Z[x] \to S$ sending $x$ to $s$ and ‘extending’ the unique ring homomorphism $\iota : \mathbb Z \to S$. In this case the commutativity of $S$ is immaterial (why?).

The unique homomorphism $f: \mathbb Z[x] \to S$, where is $x \mapsto s$, is defined by mapping $f(a_0+a_1x+\cdots+a_nx^n)=\iota(a_0)+\iota(a_1)s+\cdots +\iota(a_n)s^n$ where $\iota: \mathbb Z \to S$ is the unique ring homomorphism.

Consider $(a_0 +a_2x^2)$ and $(b_1x+b_2x^2)$. Then $(a_0 +a_2x^2)(b_1x+b_2x^2)=a_0b_1x+a_0b_2x^2+a_2b_1 x^3+a_2b_2x^4$.

So, $$f(a_0 +a_2x^2)=\iota(a_0) +\iota(a_2)s^2,$$ $$f(b_1x +b_2x^2)=\iota(b_1)s +\iota(b_2)s^2,$$ $$f(a_0b_1x+a_0b_2x^2+a_2b_1 x^3+a_2b_2x^4)=\iota(a_0b_1)s+\iota(a_0b_2)s^2+\iota(a_2b_1)s^3+\iota(a_2b_2)s^4.$$

However, \begin{align*} f(a_0 +a_2x^2)f(b_1x +b_2x^2)&=(\iota(a_0) +\iota(a_2)s^2)(\iota(b_1)s +\iota(b_2)s^2)\\ &=\iota(a_0)\iota(b_1)s+\iota(a_0)\iota(b_2)s^2+\iota(a_2)s^2\iota(b_1)s+\iota(a_2)s^2\iota(b_2)s^2. \end{align*}

If $S$ does not commute then $f$ is not a ring hom? So, why does it not matter if $S$ is commutative?

  • 3
    $\begingroup$ What you are forgetting is that $\iota(\mathbb{Z})$ always lies in the center of $S$, because it is a ring homomorphisms. So $s\iota(n) = \iota(n)s$ for all $n\in\mathbb{Z}$. $\endgroup$ Jun 10, 2019 at 20:24
  • $\begingroup$ Another way to look at it is that the free ring on $n$ elements is $\mathbb{Z} \langle t_1, \ldots, t_n \rangle$ which consists of elements of a form like $3 t_2 t_1 t_2^2 t_3^5 t_1 - 2 t_3 + 5$ where the $t_i$ do not commute with each other. It just happens that $\mathbb{Z}\langle t \rangle \simeq \mathbb{Z}[t]$ is commutative - whereas for $n \ge 2$, $\mathbb{Z}\langle t_1, t_2, \ldots, t_n \rangle$ is not commutative. $\endgroup$ Jun 10, 2019 at 20:35

2 Answers 2


The image of $\iota$ is automatically contained in the center of $S$. For example, $\iota(3) = 1_S + 1_S + 1_S$, so for any $x \in S$, we have $$\iota(3) x = (1_S + 1_S + 1_S) x = 1_S x + 1_S x + 1_S x = x + x + x = \cdots = x \iota(3).$$ (If you have not seen this result before, I will leave the formalization of the proof to you, along with the case of $\iota(n)$ for $n < 0$.)

Thus, for instance, $\iota(a_2) s^2 \iota(b_1) s = \iota(a_2) \iota(b_1) s^2 s = \iota(a_2 b_1) s^3$.


First: If $S$ is any ring with unit $1 ∈ S$, then by induction from “$1·x = x = x·1$” using distributivity, $ℤ·1$ is always within the center of $S$, so you may regard $S$ as a $ℤ$-Algebra.

If $s ∈ S$ is any element, then $s$ and all its powers commute with each other as well as with all elements of $ℤ·1$. You can show that the smallest $ℤ$-Algebra within $S$ containing $s$ is given by $$\{a_ns^n + … + a_1s + a_0;~a_0,…,a_n ∈ ℤ\}$$ and is hence commutative. Let’s call this algebra $ℤ[s]$.

Now, there is a unique $ℤ$-algebra homomorphism $ℤ[X] → ℤ[s]$ with $X ↦ s$, and an inclusion $ℤ[s] → S$, which is an injective ring homomorphism. Hence, there is always a unique ring homomorphism $ℤ[X] → S$ with $X ↦ s$.

Bottom line: Powers of a fixed element commute with each other, hence stuff generated by one element over commutative structures tend to be commutative themselves.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.